THE EXPLORATION OF PLANT SPECIES IN NATURE RESERVE OF MOUNT MUTIS EAST NUSA TENGGARA PROVINCE - Solikin Solikin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2015)
This research was aimed to explore and inventory the plant diversity, especially medicinal plants in Nature Reserve of Mount Mutis. Data were collected in Fatumnasi Village, Fatumnasi District of South Central Timor Regency in October 2011 through plant exploration and interview the local people. Plants inventory was conducted along the tracks during exploration. Herbs vegetation analysis was conducted among the tree stands of Eucalyptus urophylla. In addition, orchid vegetation analysis was only conducted to orchids that have been found attaching to Eucalyptus urophylla trees. Results showed that there were about 52 family, 78 genera and 84 species of plants in the observed area. Tree species was dominated by 'ampupu' (Eucalyptus urophylla), while orchid species was dominated by Eria retusa. Herbaceous plant communities were dominated by Centella asiatica, Cyperus sp. and Cynodon dactylon. There were about eight plant species of medicinal plants and one food plant species found in the forestthat have been known by local people.